2020
DOI: 10.1177/0265407520919992
|View full text |Cite
|
Sign up to set email alerts
|

Stress generation theory in couples with depression: A latent profile analysis

Abstract: Depressive symptoms and conflict negatively affect romantic relationships, but does this differ among couples? Using a stress generation theory framework, we aim to understand the types of profiles based on both partners’ responses of depressive symptoms and conflict. We used data from 1,598 German couples (different-sex) and conducted latent profile analyses in order to examine if there are different profiles of couples related to the male and female partners’ depressive symptoms and levels of conflict. We th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…This study extends our previous work in which we investigated dyadic classes of both partners’ depressive symptoms at one time point (Morgan et al, 2020). This is the first known study to examine dyadic classes of both partners’ depressive symptoms over time.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This study extends our previous work in which we investigated dyadic classes of both partners’ depressive symptoms at one time point (Morgan et al, 2020). This is the first known study to examine dyadic classes of both partners’ depressive symptoms over time.…”
Section: Discussionsupporting
confidence: 81%
“…Testing the heterogeneity of depression allows researchers to parse out groups of people who experience different levels of symptomatology over time. We identified one previous study that used mixture modeling on a large sample of German couples that identified four types of couples ranging in level of depressive symptoms and conflict at one point in time (Morgan et al, 2020). The study of a large population-based sample illustrated that partners and couples vary in severity of depressive symptoms.…”
Section: Couple Classes Of Depressive Symptom Trajectoriesmentioning
confidence: 99%